Genomic and Proteomic Evaluation of Tissue Quality of Porcine Wounds Treated With Negative Pressure Wound Therapy in Continuous, Noncontinuous, and Instillation Modes - Derrick, Kathleen L. (Eplasty, 2014)
Objective: Negative pressure wound therapy with instillation (NPWTi-d) combines NPWT with automated delivery and removal of topical wound treatment solutions. This porcine study compared genomic and proteomic responses of wounds treated with NPWTi-d with saline to wounds treated with NPWT in continuous and noncontinuous modes. Methods: Full-thickness porcine dorsal excisional wounds were treated with continuous NPWT, intermittent NPWT, dynamic NPWT, or NPWTi-d with saline (n = 10 wounds per group). On day 7, animals were euthanized and tissues collected. Real-time quantitative polymerase chain reaction arrays profiled expression of 84 genes including extracellular matrix remodeling factors, inflammatory cytokines and chemokines, and growth factors and major signaling molecules. Concentrations of proteins associated with angiogenesis, extracellular matrix components, and cellular energetics were analyzed via enzyme-linked immunosorbent assays. Results: Gene expression profiles for NPWTi-d with saline and continuous NPWT were similar. There were 5 upregulated and 18 downregulated genes overexpressed in NPWTi-d compared to NPWT wounds. Protein content was comparable in all treatment groups and similar to unwounded tissue. Conclusions: Previous preclinical studies have reported an increased rate of granulation tissue formation with NPWTi-d with saline compared to NPWT in continuous and noncontinuous modes. This evaluation of gene and protein expression suggests that the granulation tissue in these wounds has a similar quality. This first look at the differences in gene expression, particularly in genes related to remodeling, cell adhesion, inflammation, and growth factors, could help to clarify the observed differences in granulation rates.